Perovskite templating via a bathophenanthroline additive for efficient light-emitting devices - Jamaludin, Nur Fadilah (2019)
Identified as emerging light absorbers due to their plethora of unique optoelectronic properties, perovskites have also been touted as a promising candidate for light emission. However, despite the effortless transition of perovskites into the current organic light-emitting diodes (OLEDs), misalignment of energy levels at the hole transporting material (HTM) and perovskite interface limits the efficacy of interfacial charge transport. Herein, it is shown that by incorporating a small organic molecule, bathophenanthroline (BPhen), into the CH3NH3PbBr3 emitter via a solvent engineering technique, the energy band levels of the perovskite can be tailored and the energy mismatch at the HTM/perovskite interface can be ameliorated through the formation of a graded emitter layer and accompanying morphological improvements. With a BPhen concentration of 0.500 mg mL−1, more than ten-fold enhancement of device luminance and efficiency was achieved, thus demonstrating a facile and viable approach for fabricating high-performance perovskite light-emitting diodes (PeLEDs).